Molecular and Antigenic Characterization of the Leishmania (Viannia) panamensis Kinetoplastid Membrane Protein-11 (1998)
ABSTRACT: The kinetoplastid membrane protein 11 (KMP-11) has been recently described in Leishmania (Leishmania) donovani as a major component of the promastigote membrane. Two oligonucleotide primers were synthesized to PCR-amplify the entire coding region of New World Leishmania species. The Leishmania (Viannia) panamensis amplification product was cloned, sequenced and the putative amino acid sequence determined. A remarkably high degree of sequence homology was observed with the corresponding molecule of L. (L) donovani and L. (L) infantum (97% and 96%, respectively). Southern blot analysis showed that the KMP-11 locus is conformed by three copies of the gene. The L. (V) panamensis ORF was subsequently cloned in a high expression vector and the recombinant protein was induced and purified from Escherichia coli cultures. Immunoblot analysis showed that 80%, 77% and 100% sera from cutaneous, mucocutaneous and visceral leishmaniasis patients, respectively, recognized the recombinant KMP-11 protein. In a similar assay, 86% of asymptomatic Leishmania-infected individuals showed IgG antibodies against the rKMP-11. We propose that KMP-11 could be used as a serologic marker for infection and disease caused by Leishmania in America.